Supporting Preschoolers’ Mental Health and Academic Learning through the PROMEHS Program: A Training Study - Elisabetta Conte; Valeria Cavioni; Veronica Ornaghi; Alessia Agliati; Sabina Gandellini; Margarida Frade Santos; Anabela Caetano Santos; Celeste Simões; Ilaria Grazzani (Children, 2023)
There is compelling evidence that early school intervention programs enhance children’s development of life skills, with a positive knock-on effect on their behaviors and academic outcomes. To date, most universal interventions have displayed gains in children’s social-emotional competencies with a limited reduction in problem behaviors. This may depend on programs’ curricula focused to a greater extent on preschoolers’ social-emotional competencies rather than problem behaviors. Promoting Mental Health at Schools (PROMEHS) is a European, school-based, universal mental health program explicitly focused on both promoting students’ mental health and preventing negative conduct by adopting a whole-school approach. In this study, we set out to evaluate the effectiveness of the program for Italian and Portuguese preschoolers. We recruited 784 children (age range = 4–5 years), assigning them to either an experimental group (six months’ participation in the PROMEHS program under the guidance of their teachers, who had received ad hoc training) or a waiting list group (no intervention). We found that PROMEHS improved preschoolers’ social-emotional learning (SEL) competencies, prosocial behavior, and academic outcomes. The more practical activities were carried out at school, the more children’s SEL competencies increased, and the more their internalizing and externalizing behaviors decreased. Furthermore, marginalized and disadvantaged children were those who benefited most from the program, displaying both greater improvements in SEL and more marked decreases in internalizing problems compared to the rest of the sample.